Kajian Pengembangan Unit Usaha Klinik Hemodialisa Skala Usaha Kecil Menengah Berbasis Badan Penyelenggara Jaminan Sosial Kesehatan - Dewi, Wiwi Kania; Hubeis, Musa; Zakaria, Fransiska R (Institut Pertanian Bogor, 2017)
Indonesia is one country with the kidney failure is quite high, according to the Indonesian Society of Nephrology (PERNEFRI) in the 5th Report of Indonesian Renal Registry, in 2012 there were 16.040 patients with kidney failure but reportedly only 9161 patients were active in hemodialysis in 2012. The purpose of research is (a) identifying the internal and external factors potential business unit clinic hemodialysis-based BPJS Health, (b) develop appropriate strategies with a SWOT analysis of the business unit clinic hemodialysis-based BPJS and (c) to analyze the satisfaction of patients who use the clinic hemodialysis-based BPJS Health. Data processing and analysis using the analysis: (a) analysis matrix EFE (External Factor Evaluation) and IFE (Internal Factor Evaluation), (b) matrix Internal External (IE); (c) a SWOT analysis (Strengths, Weaknesses, Opportunities and Threats); (d) Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI). EFE value (2.73) and IFE (2.61) obtained IE matrix that shows the position of growth/stable. SWOT analysis produce six alternative development strategies that can be implemented in the development of the business unit. From the study of IPA to attribute asked to patients, it was found that the performance of the business unit is considered good, where there are nearly half of the attributes that were examined are in the second quadrant. This shows the importance of the assessment of the attributes considered important by patients and in its implementation is considered to be very good. CSI score of 0.920, indicating the level of customer satisfaction index is at 0.81 to 1.00, or interpreted the customer was very satisfied with the business unit of the hemodialysis clinics SME scale.